Penguatan Kesadaran Diri dan Pengelolaan Emosi melalui Pendekatan Psikososial pada Penyandang Disabilitas Mental - Amelia Fitri Indarti; Hanifa Putri Wardhani; Jovanka Jovanka; Siska Amalia (Lembaga Pengembangan Kinerja Dosen, 2026)
Individuals with mental disabilities commonly experience difficulties in self-awareness and emotion regulation, which negatively affect social functioning and psychosocial well-being. These conditions were also observed among beneficiaries in the assisted community, who demonstrated limitations in recognizing emotions, expressing feelings, and engaging in social interactions. This community service program aimed to strengthen self-awareness and emotional regulation skills among individuals with mental disabilities through a psychosocial approach. The program employed activity-based psychoeducation using participatory and supportive methods, including emotional recognition training, self-reflection, positive emotional stimulation, and structured group support. The results indicated improvements in beneficiaries’ ability to identify and express basic emotions, increased self-confidence, enhanced emotional stability, and more active social participation. Qualitative observations revealed behavioral changes from passive tendencies to more responsive and cooperative involvement in group activities. These findings suggest that activity-based psychosocial interventions are effective in improving psychosocial well-being among individuals with mental disabilities.